The Influence of Financial Literacy, Lifestyle, and Use of Financial Technology on Financial Management Behavior of Generation Z - Gheovani Dery Setiawan; Ratih Kusumawardhani; Johannes Maysan Damanik (PT SOLUSI EDUKASI BERDIKARI, 2026)
This study aims to analyze the influence of financial literacy, lifestyle, and the use of financial technology on financial management behavior among Generation Z students at the Faculty of Economics, Sarjanawiyata Tamansiswa University. This study used a quantitative method with an associative approach. Data were collected through questionnaires distributed to 100 respondents selected using a stratified random sampling technique. Data analysis was carried out using descriptive statistics, validity tests, reliability tests, classical assumption tests, and multiple linear regression. The results showed that financial literacy and lifestyle had no significant effect on financial management behavior, while the use of financial technology had a positive and significant effect. These findings indicate that the use of financial technology plays an important role in shaping the financial management behavior of Generation Z.